PELAYANAN PRIMA DI KANTOR SAMSAT KOTA SEMARANG - Latif Adin Raharya; Turtiantoro .; Puji Astuti (Journal of Politic and Government Studies, 2016)
Problems on Samsat Office Semarang is the service provided to the WPespecially on motor vehicle tax (PKB). The services provided do not ever meet thetargets, especially in terms of the speed at which results in complaints receivedalways exceed its target. This indicates the constraints of office SAMSATSemarang in providing excellent service to taxpayers. In order to improve thequality of services and solve problems that often occur in a public organization, ittakes a strategy of excellent service so that the service becomes b